Tanggung Gugat Notaris Terhadap Ketidaksesuaian Harga Transaksi Sewa Menyewa Tanah Berdasarkan Keterangan Palsu Para Penghadap - Gede Parwata, I Putu; Dahana, Cokorda Dalem (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 01 (2022), 2022)
The purpose of writing is to increase knowledge about the criminal responsibility of the Notary on the payment of income tax based on the false description of the applicant and the legal protection of the Notary on the actuarial of the land rental based on the false description of the pruning. The author uses a normative legal research method by instilling the emptiness of the norm, which is not regulated by the liability of the Notary criminal in the Laws of Notary, implementing a legislation approach, conceptual and analysis, as well as to use the primary, secondary and tertiary legal materials and the results are described descriptively. The results indicated that there is false description in the land rental act as the responsibility of the facer, because the Notary only imposes the will of the fighter into the actua. Notary is not authorized to investigate materialally. So that the Notary is not criminally responsible for the false description of the pruning. Legal protection for the Notary to the land rental actuas based on false information is the absence of the Notary Honorary Assembly. Each notary call is obliged to obtain the approval of the Assembly, because this assembly is the law protection institution of Notary if it is suspected to make a violation. So it is more assured if the caller, examination, detention is already agreed to the Assembly, so that the legal certainty for the Notary.